2020
DOI: 10.1002/mds.28127
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Simple Parkinson's Disease Risk Score in a LongitudinalPopulation‐BasedCohort

Abstract: Background Identifying individuals at risk of developing Parkinson's disease (PD) is critical to define target populations for future neuroprotective trials. Objective The objective of this study was to apply the PREDICT‐PD algorithm of risk indicators for PD in a prospective community‐based study (the Bruneck study), representative of the general elderly population. Methods PREDICT‐PD risk scores were calculated based on risk factor assessments obtained at baseline (2005, n = 574 participants). Cases of incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…With securing access to other cohorts' data sets in the future, we plan to assess the PREDIGT Score's discriminative performance in a similar, case-control manner (e.g., EPIPARK, 24 Harvard Biomarker Study ). We will also undertake the task of assessing its predictive performance in prospective, longitudinal studies of neurologically healthy persons, who were enrolled after having been identified as carrying one or more risk factor, a key emphasis in our field, as highlighted by Noyce et al 25 There, we will seek to interrogate results from those ongoing, (Oxford Parkinson's Disease Centre study); 29 PREDICT-PD; 30 Bruneck; 31 and Luxembourg…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With securing access to other cohorts' data sets in the future, we plan to assess the PREDIGT Score's discriminative performance in a similar, case-control manner (e.g., EPIPARK, 24 Harvard Biomarker Study ). We will also undertake the task of assessing its predictive performance in prospective, longitudinal studies of neurologically healthy persons, who were enrolled after having been identified as carrying one or more risk factor, a key emphasis in our field, as highlighted by Noyce et al 25 There, we will seek to interrogate results from those ongoing, (Oxford Parkinson's Disease Centre study); 29 PREDICT-PD; 30 Bruneck; 31 and Luxembourg…”
Section: Discussionmentioning
confidence: 99%
“…g ., EPIPARK, 24 Harvard Biomarker Study 22 ). We will also undertake the task of assessing its predictive performance in prospective, longitudinal studies of neurologically healthy persons, who were enrolled after having been identified as carrying one or more risk factor, a key emphasis in our field, as highlighted by Noyce et al 25 There, we will seek to interrogate results from those ongoing, regional cohorts where sufficient data on variables needed for the calculation of the PREDIGT Score have been collected, such as in: PRIPS (Prospective validation of risk factors for the development of Parkinson syndromes); 26 TREND (Tübingen-based evaluation of risk factors in the early detection of neurodegeneration); 27 PARS (Parkinson At-Risk Syndrome); 28 OPDC (Oxford Parkinson’s Disease Centre study); 29 PREDICT-PD; 30 Bruneck; 31 and Luxembourg Parkinson’s Study. 32…”
Section: Discussionmentioning
confidence: 99%
“…The PREDICT-PD algorithm incorporates remotely-assessable early non-motor features and risk factors combined into a risk score that in the original study was associated with incident PD during follow-up over 3 years with a hazard ratio of 4.4 [ 27 ]. Two validation attempts showed weaker, but significant associations of the score with incident PD, with odds ratios of 1.3–2.1 [ 30 , 31 ]. An enhanced PREDICT-PD risk score has recently been developed that integrates three additional markers and showed better accuracy in predicting PD compared with the original score [ 32 ].…”
Section: Identifying Prodromal Pd As a Target Population For Disease-...mentioning
confidence: 99%
“…If we again take the example of the association between diet and PD, appropriate adjustment for smoking is necessary because smoking behavior is associated with both diet and PD risk and thus could be a confounder in this association (39,45). In addition, broad data collection provides the opportunity to study the interdependence of markers of pre-diagnostic PD (46,47) and to combine multiple markers in a prediction algorithm for PD (48)(49)(50)(51)(52)(53)(54), such as the PREDICT-PD algorithm (55,56) and the naïve Bayesian classifier approach of the MDS research criteria for prodromal PD (54). Finally, the large datasets of population-based studies offer possibilities to study the combined effect of multiple risk factors on PD, as well as on clusters of chronic diseases (57), which is essential given that many risk factors and chronic diseases co-occur.…”
Section: Importance Of Population-based Studies In Pre-diagnostic Parkinson's Diseasementioning
confidence: 99%